একাল সেকাল : পাঁচ প্রজন্মের ইতিকথা - রায়, ভারতী (কলকাতা : আনন্দ, 2008)
Autobiography of a woman college professor, historian, and vice-chancellor from Calcutta, India.
Donated By Akbar Ali Khan
Keywords: Ray, Bharati; Women college teachers -- India -- Kolkata -- Biography; Women historians -- India -- Kolkata -- Biography